Giant hysteromyoma after vaginoplasty in a woman with Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome: case report and review of the literature. Issue 12 (December 2021) - Qiu, Shikang; Xie, Yunkai; Zou, Yonghui; Wang, Fei
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a congenital disorder characterized by congenital absence of both the uterus and vagina. Some patients require surgery to create a neovagina, however, the preservation of a nonfunctional rudimentary uterus after surgery may lead to long-term complications. Herein, a rare case of a giant hysteromyoma after vaginoplasty, in a 31-year-old Chinese female patient who was diagnosed with MRKH syndrome, is reported. The patient, who had undergone vaginal reconstruction 4 years previously, presented with abdominal distension for the previous 2 weeks. Transabdominal ultrasonography showed a firm mass of approximately 10 × 10 cm in the lower abdomen. The patient subsequently underwent an exploratory laparotomy, and a leiomyoma from her rudimentary uterus was removed. Beside this case, seven cases, published between 2004 and 2020, were identified during a literature search. Findings of the present and previously published cases suggest that gynaecologists should pay particular attention to the risks of pelvic complications in female patients with MRKH syndrome who have previously undergone surgery, and select appropriate therapeutic methods.